The Role of Internal Audit in Preventing Mosque Financial Reporting Fraud at the Grand Mosque as a Sharia Tourism Destination in Soloraya - Julia Noermawati Eka Satyarini; Rozikan, Rozikan; Wahyu Wismawati; Maddani Akhsa Nulyani (International Journal of Economics, Business and Innovation Research, 2025)
Mosque as a non-profit organization, plays a pivotal role in its function as a place of worship. Additionally, it serves a significant role in supporting social activities, tourism, education, and other activities in accordance with Islamic law. To address the demands of transparency and accountability, it is imperative that mosques prepare accurate financial reports in accordance with relevant accounting standards. However, the implementation of these practices is often hindered by limited resources. This study aims to analyze the role of internal audit in preventing fraudulent financial reporting of mosques in accordance with relevant accounting standards, with a focus on the grand mosques of sharia tourism destinations in Soloraya, namely Al-Falah Sragen Grand Mosque, Madaniyah Grand Mosque Karanganyar, and Al-Aqsha Mosque Klaten. This research uses descriptive qualitative methods with primary and secondary data as sources through observation, interviews, and documentation. The results indicated that while the mosques have prepared financial statements in accordance with sharia accounting principles, such as accountability, fairness, and truth, their accounting practices are not yet fully aligned with the accounting standards of non-profit entities. Internal audits, though still rudimentary in some mosques, contribute to fraud prevention by providing basic oversight mechanisms. The involvement of professional organizations like LAZISMU at Masjid Raya Al-Falah Sragen exemplifies effective financial management. However, other mosques rely on simpler approval mechanisms by mosque management or local government supervision.